2009
DOI: 10.5194/bg-6-1311-2009
|View full text |Cite
|
Sign up to set email alerts
|

Soil, plant, and transport influences on methane in a subalpine forest under high ultraviolet irradiance

Abstract: Abstract. Recent studies have demonstrated direct methane emission from plant foliage under aerobic conditions, particularly under high ultraviolet (UV) irradiance. We examined the potential importance of this phenomenon in a high-elevation conifer forest using micrometeorological techniques. Vertical profiles of methane and carbon dioxide in forest air were monitored every 2 h for 6 weeks in summer 2007. Day to day variability in above-canopy CH 4 was high, with observed values in the range 1790 to 1910 nmol … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 63 publications
4
24
0
Order By: Relevance
“…Accordingly, the Allan variance has a characteristic "V-shape" defined by the whitenoise dominated region at short integration times and by the domain of various drift effects at longer integration times. Our results are consistent with other recent work (Kroon et al, 2007;Smeets et al, 2009;Eugster and Plüss, 2010;Bowling et al, 2009), suggesting that the achievable detection limit for methane with the existing analyzers is about 1 to 5 ppb Hz −1/2 , which implies that variations of 0.05% in ambient methane mixing ratio are readily captured. The only strikingly different Allan variance plot has recently been published by Hendriks et al (2008).…”
Section: Precisionsupporting
confidence: 92%
“…Accordingly, the Allan variance has a characteristic "V-shape" defined by the whitenoise dominated region at short integration times and by the domain of various drift effects at longer integration times. Our results are consistent with other recent work (Kroon et al, 2007;Smeets et al, 2009;Eugster and Plüss, 2010;Bowling et al, 2009), suggesting that the achievable detection limit for methane with the existing analyzers is about 1 to 5 ppb Hz −1/2 , which implies that variations of 0.05% in ambient methane mixing ratio are readily captured. The only strikingly different Allan variance plot has recently been published by Hendriks et al (2008).…”
Section: Precisionsupporting
confidence: 92%
“…Several studies have reported opposite results that no measurable CH 4 release from plants was detected (Beerling et al, 2008;Bowling et al, 2009;Dueck et al, 2007;Kirschbaum and Walcroft, 2008;Nisbet et al, 2009;Smeets et al, 2009;Takahashi et al, 2012). One potential explanation for the absence of CH 4 emissions is that the CH 4 produced was consumed by endophytic methanotrophs.…”
Section: Uncertainties and Limitationsmentioning
confidence: 98%
“…pectin, lignin, cellulose and leaf surface wax) (Bruhn et al, 2014;Keppler et al, 2008;McLeod et al, 2008;Messenger et al, 2009;Vigano et al, 2009Vigano et al, , 2008 have been extensively tested. The majority of studies reported substantial CH 4 emissions, while Bowling et al (2009) reported no evidence for substantial CH 4 emissions by a conifer forest under high UV radiation, to which a soil CH 4 sink might contribute. There seems to be a linear relationship between the CH 4 emission rate and the UV radiance intensity and an exponential relationship between CH 4 emission rates and temperature.…”
Section: Plantsmentioning
confidence: 99%
“…The global methane production rates from living plants were estimated to be 62-236 Tg CH 4 year −1 , which may have a considerable effect on the global methane budget. This study generated a vigorous scientific debate and many subsequent studies were performed (e.g., Kirschbaum et al 2006;Kitaoka et al 2007;Beerling et al 2008;Kirschbaum and Walcroft 2008;Bowling et al 2009). In subsequent experiments, emission rates were found to be quite distinct in each experiment (e.g., Keppler et al 2006;Kirschbaum et al 2006;Kitaoka et al 2007), and some studies failed to measure any emissions (Beerling et al 2008;Kirschbaum and Walcroft 2008).…”
Section: Introductionmentioning
confidence: 99%